Glycaemic Index After Cooking Potatoes and Gluten Rice - Wiwik Wijaningsih; Heni Hendriyani; Setyo Prihatin (Poltekkes Kemenkes Semarang, 2014)
Tthe study was to examine effect of cooking methods on glycaemic index of potatoes and gluten rice. Randomized experiment with one treatment group was conducted. The treatment was consumption of food with three different cooking methods, including boiled, boiled plus fat, and boiled with fat and protein. Sample was 30 healthy teenager women. Blood glucose levels were measured at 0, 30, 60, 90, 120 minutes after consumption of these foods using glucometer. GI of boiled potatoes, parsley potatoes and hush brown were 81,78, 72,69 and 69,47 at 0, 30, 60, 90, 120 minutes after consumption, respectively. GIs of boiled gluten rice, boiled gluten rice plus fat, and boiled gluten rice with fat and protein were 149.17, 75.17, and 71,59, respectively. Inclussion: the GIs of potatoes and gluten rice can be reduced by adding fat and protein